PERSEPSI AL-QUR’AN TERHADAP ILMU PENGETAHUAN (Konstruksi Ilmu Pengetahuan dalam Perspektif Filsafat Ilmu) - Rohani, Edi (AL-QALAM: JURNAL KEPENDIDIKAN, 2024)
The Qur’an, as the kalām Allāh (Word of God) and maṣdār al-tasyrī’ (primary source) of Islamic teachings, does not merely regulate matters of worship (‘ubūdiyah), but also provides significant signals and messages related to knowledge. In the Qur’an, the word "al-’ilm" (knowledge) is mentioned at least 105 times, or 744 times in various derivative forms. This term is used to signify the process of acquiring knowledge. Utilizing a library research method and a qualitative descriptive research model, this study philosophically aims to explore the origin of knowledge, the construction of knowledge from the Qur’anic perspective, and the ways to acquire and utilize knowledge in human life. From the perspective of the philosophy of knowledge, the construction of knowledge in the Qur’an can be examined through the dimensions of ontology, epistemology, and axiology. The Qur’anic conception of knowledge integrates both spiritual and rational dimensions, where knowledge is obtained through reason and revelation. The Qur’an encourages the use of reason to understand reality and attain truth, while also providing ethical and spiritual guidance. Epistemologically, knowledge in the Qur’an is constructed through the integration of bayānī reasoning (textual explanation), ‘irfānī reasoning (intuitive knowledge), and burhānī reasoning (logical reasoning). These three systems complement each other in understanding knowledge within the Qur’anic framework.